Avaliação da atividade antibacteriana de nisina e nanopartículas de curcumina frente a bactérias de interesse em alimentos - Quichaba, Michely Bião (2021)
Pathogenic bacteria and viruses are responsible for the largest number of foodborne illnesses (FI) outbreaks worldwide, in which Staphylococcus aureus, Salmonella Typhimurium and Escherichia coli stand out. Increasing attention has been paid to the use of natural preservatives, which extend shelf life and improve food safety. Among the numerous natural preservatives that have antimicrobial activity, nisin, a bacteriocin widely used in the food industry, and curcumin, an orange pigment extracted from saffron, stand out. However, such compounds have low water solubility, which impairs both their application and their action in food. Nanoencapsulation has been widely studied as an alternative to increase solubility, in addition to optimizing the antibacterial activity of compounds. In this context, it is expected that the encapsulation of curcumin and its co¬encapsulation with other natural compounds can improve the viability of application in food, in addition to its action. Thus, the present work aimed to evaluate the antibacterial activity by determining the Minimum Inhibitory Concentration (MIC) and the Minimum Bactericidal Concentration (MBC) of nisin (Nis) and curcumin nanoparticles (NCur, produced by the solid dispersion technique, with polyvinylpyrrolidone as an encapsulant and Tween 80 as a surfactant) against the bacteria S. aureus, E. coli and S. Typhimurium. In addition, the effect of the association of NCur and together with Nis against the same microorganisms was evaluated by fractional inhibitory concentration (FIC). It was found that both NCur and Nis had MIC (NCur = 0.75 mg/mL and Nis = 0.5 mg/mL) and MBC (NCur = 0.75 mg/L and Nis = 1.0 mg/mL) mL) smaller against S. aureus, in addition to presenting synergism when tested against this bacterium (FIC = 0.265). In the next step, the coencapsulation of curcumin and nisin (NCurNis) was performed, using the ratio found in the synergism (1:1.36 (mcurcumin/mnisin)) and the coencapsulation was evaluated for MIC and MBC again against S. aureus, resulting in a MIC of 0.064 mg/mL, showing a better inhibitory effect, when comparing NCur and nisin alone. However, it was not possible to determine the MBC for this case. The nanoparticles were also characterized as to their physicochemical properties, where it was verified by Differential Scanning Calorimetry and Thermogravimetric Analysis that for the NCur the components were completely miscible and in amorphous form (without the presence of the crystalline melting peak of curcumin), in addition to detecting interactions between encapsulant/encapsulated by Fourier Transform Infrared Spectroscopy. In the case of NCurNis, interactions between encapsulant/ encapsulates were not determined at the same level as NCur, despite the formation of nanometric structures (Transmission Electron Microscopy and Dynamic Light Scattering), indicating that the encapsulation was possibly not complete. Thus, NCurNis have potential for further investigations regarding coencapsulation and action.